INTERNET FINANCIAL REPORTING: A SYSTEMATIC LITERATURE REVIEW - Muhammad Hamdan Sayadi; Falikhatun (Media Riset Akuntansi, Auditing & Informasi, 2023)
This study aims to develop a study of specific features by examining current developments in online reporting. This is important to improve researchers' understanding of the development of the topic "Internet Financial Reporting". A comprehensive review of the existing literature disclosure index shows that different researchers use different dimensions to represent the IFR index. These differences contribute to the variation of findings among researchers and have not been able toclearly summarize the phenomenon and its determinants. Therefore, the dimensions of the IFR disclosure index are important to study. This study specifically analyzes papers published in scopus. The most widely used disclosure index criterion in IFR is to distinguish the content and presentation of IFR (eight researchers). Then, there were two researchers who used the total IFR criteria. Previous research has also distinguished the criteria for disclosure index into financial and non-financial information and distinguished the disclosure index criteria into IFR and IFR content in general. Then, previous studies have also used 3 IFR disclosure indices at once consisting of dummy, degree IFR, and scope IFR. In addition, some researchers only use 1 IFR disclosure index. Further research is expected to use intervening and moderating variables in IFR research.